Is Single LIMA-LAD Bypass Appropriate for OPCAB Training? - Naito, Shiho; Reichenspurner, Hermann; Sill, Björn (The Thoracic and Cardiovascular Surgeon, 2024)
Background A significant impact of surgeons' experience on outcomes of off-pump coronary artery bypass (OPCAB) has been recognized through previous large-scale studies. However, a safe, effective, and concrete OPCAB training was yet to be identified. We evaluate a safety of our OPCAB training model with single left internal mammary artery (LIMA)–left anterior descending artery (LAD) as a reasonable first step.Methods Between January 2010 and June 2019, 180 patients with an isolated single coronary bypass of the LAD using LIMA as an in situ graft via median sternotomy fulfilled the inclusion criteria. Coronary arterial bypass under cardiopulmonary bypass (CPB), utilizing other graft material, minimal invasive direct coronary arterial bypass through left-sided thoracotomy, and multiple diseased coronary artery disease were excluded. The primary outcome is an early postoperative outcome (major adverse cardiac and cerebrovascular events [MACCEs]: myocardial infarction, coronary re-revascularization, stroke, acute renal failure, and all causes of death) between residents in training under supervision (group 1: n = 63) and experienced surgeons (group 2: n = 117). Trainees were already experienced in on-pump coronary artery bypass grafting.Results Preoperative variables were comparable. There was no significant difference in the rate of MACCEs between the two groups including hospital mortality (p = 1.000), perioperative myocardial infarction (p = 0.246), stroke (p = 0.655), and acute renal failure (p = 0.175).Conclusion The early postoperative outcome of off-pump LIMA to the LAD performed by trainees was comparable to those by experienced surgeons. Single LIMA-LAD was safely performed by trainees under supervision without CPB. In order to master OPCAB technique, single LAD bypass might be a reasonable first step to get into touch with the technical characteristics of this special procedure.
Keywords: off-pump coronary artery bypass; training; LIMA-LAD